Low Band Gap Benzimidazole COF Supported Ni3N as Highly Active OER Catalyst. Issue 24 (29th August 2016) - Nandi, Shyamapada; Singh, Santosh Kumar; Mullangi, Dinesh; Illathvalappil, Rajith; George, Leena; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan
Abstract : Covalent organic frameworks (COFs) have structures and morphologies closely resembling graphenes, whose modular construction permits atomic‐level manipulations. This, combined with their porous structure, makes them excellent catalyst supports. Here, the high electrocatalytic activity of a composite, formed by supporting Ni3 N nanoparticles on a benzimidazole COF, for oxygen evolution reaction is shown. The composite oxidizes alkaline water with a near‐record low overpotential of 230 mV @ 10 mA cm −2 ( η 10 ). This high activity is attributed to the ability of the COF to confine the Ni3 N nanoparticles to size regimes otherwise difficult to obtain and to its low band gap character (1.49 eV) arising from the synergy between the conducting Ni3 N nanoparticles and the π‐conjugated COF. The COF itself, as a metal‐free self‐standing framework, has an oxygen evolution reaction activity with η 10 of 400 mV. The periodic structure of the COF makes it serve as a matrix to disperse the catalytically active Ni3 N nanoparticles favoring their high accessibility and thereby good charge‐transport within the composite. This is evident from the amount of O2 evolved (230 mmol h −1 g −1 ), which, to the best of our knowledge, is the highest reported. The work reveals the emergence of COF as supports for electrocatalysts. Abstract : A low band gap benzimidazole based covalent organic framework supported by hexagonal Ni3 N nanoparticles showing near‐record low overpotential for OER at high current densities.